British investment overseas 1870 - 1913 a modern portfolio theory approach - Goetzmann, William N. 1956-; Ukhov, Andrey (National Bureau of Economic Research, 2005)
"Many scholars have asked whether British investors benefited from overseas investment investing in the 19th century and whether this export of capital had negative effects. We re-visit the issue using modern portfolio theory. We examine the set of investment opportunities available to British investors, the developments in information transmission technology, and advances in financial and investment theory at the time. We use mean-variance optimization techniques to take into account the risk and return characteristics of domestic and international investments available to a British investor, and to quantify the beneifts from international diversification. Evidence suggests that capital export was a consequence of both the opportunity and the understanding of diversification. foreign assets offered higher rates of return, but equally important, they offered significant diversification benefits. Even when--by setting expected return on each foreign asset class equal to that of the corresponding UK asset class--we put foreign assets at a disadvantage, we find that it was rational for a British investor to include foreign debts and equity in the portfolio"--National Bureau of Economic Research web site.
Keywords: Außenpolitik; Geschichte; Investments, Foreign -- Great Britain -- History; Portfolio management -- Great Britain -- History; Großbritannien; USA; United States -- Foreign relations -- Treaties